Agile Methods in Game Programming based on Scrum - MERCAN, Şahin; BECERİKLİ, Yaşar (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2020)
Game programming requirements, which is one of the problems of game programming in recent times, is constantly changing. Therefore, the process we are conducting while programming the game does not keep up with this change leads to the failure of the product we develop or the result of higher costs. Therefore, the use of agile programming, which brings a more dynamic and modern solution to changing environment conditions, is increasing day by day and the project teams are transitioning to these processes. In this thesis, firstly historical development, content, rules and methods of Agile methods are presented with literature researches. In the next section, Grumpy Ball is applied by using Scrum method which is agile programming method. Since the agile methods provide dynamic solutions, an end date cannot be determined Therefore, the aim of this article is to determine the exact date of a game application using agile method. For this reason, our project is divided into specific parts and the last periods given to these parts were compared according to certain criteria. In the light of the results, determinations were made.